The Home Place. - Morris, Wright, 1910-1998 (UNP - Bison Books, 2014)
Reproduced from the 1948 edition of The Home Place, the Bison Book edition brings back into print an important early work by one of the most highly regarded of contemporary American Writers. This account in first-person narrative and photographs of the one-day visit of Clyde Muncy to ""the home place"" at Lone Tree, Nebraska, has been called ""as near to a new fiction form as you could get."" Both prose and pictures are homely: worn linoleum, an old man's shoes, well-used kitchen utensils, and weathered siding. Muncy's journey of discovery takes the measure of the man he has bec.